2021
DOI: 10.1186/s12910-021-00626-2
|View full text |Cite
|
Sign up to set email alerts
|

Cultural sensitivity in brain death determination: a necessity in end-of-life decisions in Japan

Abstract: Background In an increasingly globalized world, legal protocols related to health care that are both effective and culturally sensitive are paramount in providing excellent quality of care as well as protection for physicians tasked with decision making. Here, we analyze the current medicolegal status of brain death diagnosis with regard to end-of-life care in Japan, China, and South Korea from the perspectives of front-line health care workers. Main body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Our findings indicate that the time from admission to organ procurement in Japan is longer than that reported in other countries [ 15 , 16 ]. This variation may be attributed to the extensive discussions required around end-of-life care options, including organ donation, which are further complicated by the cultural emphasis on family involvement in medical decision-making processes [ 17 ]. Moreover, we noted that donors who underwent ECPR experienced longer delays to organ procurement compared to those who did not receive ECPR.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that the time from admission to organ procurement in Japan is longer than that reported in other countries [ 15 , 16 ]. This variation may be attributed to the extensive discussions required around end-of-life care options, including organ donation, which are further complicated by the cultural emphasis on family involvement in medical decision-making processes [ 17 ]. Moreover, we noted that donors who underwent ECPR experienced longer delays to organ procurement compared to those who did not receive ECPR.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to add courses related to brain death and organ donation in medical education. However, some studies have shown that there was only mild correlation between knowledge and attitude about brain-death organ donation [8,12], while the attitude was also in uenced by cultural and family factors [4,5,17]. Therefore, the courses about brain death should not only focus on the knowledge of brain death.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural and religious traditions have been referenced to explain that Asians are less likely to approve of brain death or organ transplant from brain dead donors [4,5]. However, the lack of knowledge about brain death and organ donation among health professionals and the public in China might be another important factor [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Japan there is societal resistance to the concept of brain death, and Japan has amended its law to allow individuals to declare their acceptance of brain death for the purposes of organ donation alone, although family may override this. 3 …”
Section: Why Is a Legal Definition Of Death Needed And What Are The L...mentioning
confidence: 99%